¿Son stakeholders los consumidores? - De la Cuesta Rute, José María (Revista de Derecho, 2019)
The present work is directed towards the analysis of whether the currently growing concern for the so-called consumers and users in the field of mercantile law coincides or not with the also growing attention to entrepreneurial or corporate social responsibility. To this means applies what could be held as an “amplified notion” and a “restrictive or strict notion” of consumer. None of these notions postulates that mercantile law has to echo entrepreneurial social responsibility, whose justification, on the other side, is more than debatable. The consideration of consumers in a wide sense as stakeholders does not add much to the correct economical concept of entrepreneur and competitive market and it therefore does not add much to mercantile law, which by definition, refers to those economical phenomenon. A restrictive notion of consumer which could be identified with the integrates in a group of stakeholders is not consistent with the system of market economy neither is it necessary for institutions of mercantile law to comply with their duties, nor, least of all to form a Law of consumption as a systematic judicial branch.